Diverse, ethical, collaborative leadership through revitalized cultural archetype: the Mary alternative - Rothausen, Teresa J. (Journal of business ethics, 2023)
Leadership archetypes are embodied and emotionally powerful identity profiles related to cultural conceptualizations of leadership and implicit leadership theories. The currently dominant archetype reinforces "think leader, think male" and racial biases that have been long- and well-documented in leadership research, and more recently highlighted as integrated into ethical leadership models. The pervasiveness of the archetype of leaders as agentic solo heroes leading through competition and power over others blinds us to other ways of leading. Unpacking archetype reveals that our culturally dominant narrative is what restricts leadership to a narrow group of people, creating the misperception of a shortage of leadership talent. The dominant cultural archetype is traced back through time to figures in culturally foundational texts, and forward in time to modern stories, art, and media. An alternative leadership archetype is developed through historical and theological analysis, revealing a leadership archetype in Mary of Nazareth as a young, pregnant, ethnically oppressed leader, and her Magnificat as a leadership vision statement oriented toward justice and the common good. This analysis revitalizes a neglected implicit theory or archetype of leadership, which had been crushed under layers of patriarchy, comprising leadership through supportive, creative collaboration; self-named holistic identity; feminine voice and values; justice-based vision; and a contemplative spiritual foundation. Implications for business ethics, organizations, and leadership are discussed.